2009 12th Euromicro Conference on Digital System Design, Architectures, Methods and Tools 2009
DOI: 10.1109/dsd.2009.218
|View full text |Cite
|
Sign up to set email alerts
|

Robustness Check for Multiple Faults Using Formal Techniques

Abstract: Feature sizes in VLSI circuits are steadily shrinking. This results in increasing susceptibility to soft errors, e.g. due to environmental radiation. Precautions against soft errors can be taken on all design stages, e.g. the architectural level, algorithmic level, or on the layout level. Whether the final implementation contains flaws or really provides robustness to soft errors remains to be checked.Here, we propose an approach to formally verify the robustness of a circuit with respect to multiple soft erro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…Further, the study applied the Chow and Breush-Pagan tests to decide whether pooled OLS (Ordinary Least Square) or the fixed and random effects model suggested by Pindado and Requejo (2015). Thus, the study employed the fully modified ordinary least square (FMOLS) and the dynamic ordinary least square (DOLS) panel estimate methods to check the robustness of the main findings as Rahman et al (2021), Lu andWhite (2014), andFrehse et al (2009). The findings revealed that the corporate tax rate (CTR) is positively and significantly related to the sustainable development goal (SDG) using a random effect.…”
Section: Introductionmentioning
confidence: 99%
“…Further, the study applied the Chow and Breush-Pagan tests to decide whether pooled OLS (Ordinary Least Square) or the fixed and random effects model suggested by Pindado and Requejo (2015). Thus, the study employed the fully modified ordinary least square (FMOLS) and the dynamic ordinary least square (DOLS) panel estimate methods to check the robustness of the main findings as Rahman et al (2021), Lu andWhite (2014), andFrehse et al (2009). The findings revealed that the corporate tax rate (CTR) is positively and significantly related to the sustainable development goal (SDG) using a random effect.…”
Section: Introductionmentioning
confidence: 99%
“…Dagegen kann die Anwendung formaler Methoden den Nachweis liefern, dass in jedem Systemzustand und unter allen Eingaben garantiert jede interne Fehlfunktion [6], anwendungsbezogene Restriktionen zu berücksichtigen [14], sowie das Versagen mehrerer Komponenten zu analysieren [7]. Die Analyse kann sowohl auf den sequentiellen Äquivalenzvergleich (engl.…”
Section: Introductionunclassified
“…With increasing values of t d more components are classified until the bounds meet at 70%. The initial model has been extended by an approximation of reachable states [9], an analysis of multiple faults [10], and a measure to identify hot-spots in the design [11]. The diagnosis environment RobuCheck [12] integrates different engines to perform the analyses.…”
mentioning
confidence: 99%